Ethical Implications of Animal Biotechnology: Considerations for Animal Welfare Decision Making - Thompson, Paul B.; Bazer, Fuller W.; Einsiedel, Edna F.; Riley, Margaret Foster (Council for Agricultural Science and Technology (CAST), 2010)
Animal biotechnology, which includes both genetic engineering and mammalian cloning, has expanded rapidly in recent decades. These technologies already have been applied in biomedical research and now are nearing application within the food system. This paper from CAST (IP 46) reviews animal biotechnology techniques, discusses related key ethical issues, evaluates religious views and traditions regarding animal biotechnology, summarizes public opinion research on the topic, and evaluates the challenges and opportunities for the ethical development of agricultural animal biotechnology.